Westonci.ca is the premier destination for reliable answers to your questions, provided by a community of experts. Explore thousands of questions and answers from a knowledgeable community of experts on our user-friendly platform. Discover detailed answers to your questions from a wide network of experts on our comprehensive Q&A platform.
Sagot :
To solve the given system of linear equations using Gaussian elimination with back-substitution, we will follow these steps:
1. Write the augmented matrix for the system of equations:
[tex]\[ \begin{aligned} 3x - 2y + z &= 11 \\ -x + y + 2z &= -11 \\ x - y - 4z &= 17 \end{aligned} \][/tex]
The augmented matrix representing this system is:
[tex]\[ \left[\begin{array}{ccc|c} 3 & -2 & 1 & 11 \\ -1 & 1 & 2 & -11 \\ 1 & -1 & -4 & 17 \end{array}\right] \][/tex]
2. Perform Gaussian elimination to transform the matrix into an upper triangular form.
- Normalize the first row by dividing by the pivot element (3):
[tex]\[ \left[\begin{array}{ccc|c} 1 & -0.6667 & 0.3333 & 3.6667 \\ -1 & 1 & 2 & -11 \\ 1 & -1 & -4 & 17 \end{array}\right] \][/tex]
- Eliminate the entries below the pivot in column 1:
[tex]\[ \left[\begin{array}{ccc|c} 1 & -0.6667 & 0.3333 & 3.6667 \\ 0 & 0.3333 & 2.3333 & -7.3333 \\ 0 & -0.3333 & -4.3333 & 13.3333 \end{array}\right] \][/tex]
- Normalize the second row by dividing by the pivot element (0.3333):
[tex]\[ \left[\begin{array}{ccc|c} 1 & -0.6667 & 0.3333 & 3.6667 \\ 0 & 1 & 7 & -22 \\ 0 & -0.3333 & -4.3333 & 13.3333 \end{array}\right] \][/tex]
- Eliminate the entries below the pivot in column 2:
[tex]\[ \left[\begin{array}{ccc|c} 1 & -0.6667 & 0.3333 & 3.6667 \\ 0 & 1 & 7 & -22 \\ 0 & 0 & -2 & 6 \end{array}\right] \][/tex]
- Normalize the third row by dividing by the pivot element (-2):
[tex]\[ \left[\begin{array}{ccc|c} 1 & -0.6667 & 0.3333 & 3.6667 \\ 0 & 1 & 7 & -22 \\ 0 & 0 & 1 & -3 \end{array}\right] \][/tex]
3. Perform back-substitution to find the values of [tex]\(x, y,\)[/tex] and [tex]\(z\)[/tex].
- From the third row:
[tex]\[ z = -3 \][/tex]
- Substitute [tex]\(z = -3\)[/tex] into the second row equation:
[tex]\[ y + 7(-3) = -22 \implies y - 21 = -22 \implies y = -1 \][/tex]
- Substitute [tex]\( y = -1 \)[/tex] and [tex]\( z = -3 \)[/tex] into the first row equation:
[tex]\[ x - 0.6667(-1) + 0.3333(-3) = 3.6667 \implies x + 0.6667 - 1 = 3.6667 \implies x + 0.6667 = 4.6667 \implies x = 4 \][/tex]
So, the solution to the system of equations is:
[tex]\[ (x, y, z) = (4, -1, -3) \][/tex]
1. Write the augmented matrix for the system of equations:
[tex]\[ \begin{aligned} 3x - 2y + z &= 11 \\ -x + y + 2z &= -11 \\ x - y - 4z &= 17 \end{aligned} \][/tex]
The augmented matrix representing this system is:
[tex]\[ \left[\begin{array}{ccc|c} 3 & -2 & 1 & 11 \\ -1 & 1 & 2 & -11 \\ 1 & -1 & -4 & 17 \end{array}\right] \][/tex]
2. Perform Gaussian elimination to transform the matrix into an upper triangular form.
- Normalize the first row by dividing by the pivot element (3):
[tex]\[ \left[\begin{array}{ccc|c} 1 & -0.6667 & 0.3333 & 3.6667 \\ -1 & 1 & 2 & -11 \\ 1 & -1 & -4 & 17 \end{array}\right] \][/tex]
- Eliminate the entries below the pivot in column 1:
[tex]\[ \left[\begin{array}{ccc|c} 1 & -0.6667 & 0.3333 & 3.6667 \\ 0 & 0.3333 & 2.3333 & -7.3333 \\ 0 & -0.3333 & -4.3333 & 13.3333 \end{array}\right] \][/tex]
- Normalize the second row by dividing by the pivot element (0.3333):
[tex]\[ \left[\begin{array}{ccc|c} 1 & -0.6667 & 0.3333 & 3.6667 \\ 0 & 1 & 7 & -22 \\ 0 & -0.3333 & -4.3333 & 13.3333 \end{array}\right] \][/tex]
- Eliminate the entries below the pivot in column 2:
[tex]\[ \left[\begin{array}{ccc|c} 1 & -0.6667 & 0.3333 & 3.6667 \\ 0 & 1 & 7 & -22 \\ 0 & 0 & -2 & 6 \end{array}\right] \][/tex]
- Normalize the third row by dividing by the pivot element (-2):
[tex]\[ \left[\begin{array}{ccc|c} 1 & -0.6667 & 0.3333 & 3.6667 \\ 0 & 1 & 7 & -22 \\ 0 & 0 & 1 & -3 \end{array}\right] \][/tex]
3. Perform back-substitution to find the values of [tex]\(x, y,\)[/tex] and [tex]\(z\)[/tex].
- From the third row:
[tex]\[ z = -3 \][/tex]
- Substitute [tex]\(z = -3\)[/tex] into the second row equation:
[tex]\[ y + 7(-3) = -22 \implies y - 21 = -22 \implies y = -1 \][/tex]
- Substitute [tex]\( y = -1 \)[/tex] and [tex]\( z = -3 \)[/tex] into the first row equation:
[tex]\[ x - 0.6667(-1) + 0.3333(-3) = 3.6667 \implies x + 0.6667 - 1 = 3.6667 \implies x + 0.6667 = 4.6667 \implies x = 4 \][/tex]
So, the solution to the system of equations is:
[tex]\[ (x, y, z) = (4, -1, -3) \][/tex]
We hope this was helpful. Please come back whenever you need more information or answers to your queries. We appreciate your visit. Our platform is always here to offer accurate and reliable answers. Return anytime. Westonci.ca is here to provide the answers you seek. Return often for more expert solutions.